Modulation of Follistatin and Myostatin Propeptide by Anabolic Steroids and Gender - Mosler, S.; Geisler, S.; Hengevoss, J.; Schiffer, T.; Piechotta, M.; Adler, M.; Diel, P. (International Journal of Sports Medicine, 2013)
The purpose of this pilot study was to investigate the impact of training, anabolic steroids and endogenous hormones on myostatin-interacting proteins in order to identify manipulations of myostatin signalling. To identify whether analysis of the myostatin interacting proteins follistatin and myostatin propeptide is suitable to detect the abuse of anabolic steroids, their serum concentrations were monitored in untrained males, bodybuilders using anabolic steroids and natural bodybuilders. In addition, we analysed follistatin and myostatin propeptide serum proteins in females during menstrual cycle. Our results showed increased follistatin concentrations in response to anabolic steroids. Furthermore, variations of sex steroid levels during the menstrual cycle had no impact on the expression of follistatin and myostatin propetide. In addition, we identified gender differences in the basal expression of the investigated proteins. In general, follistatin and myostatin propeptide concentrations were relatively stable within the same individual both in males and females. In conclusion, the current findings provide an insight into gender differences in myostatin-interacting proteins and their regulation in response to anabolic steroids and endogenous hormones. Therefore our data provide new aspects for the development of doping prevention strategies.
Keywords: anabolic steroids; doping; follistatin; immuno-PCR; myostatin; myostatin propeptide